2012
DOI: 10.1177/1474515112439964
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of heart failure self-care behaviour in community-based patients: a cross-sectional study

Abstract: In this exploratory cross-sectional study, the potential non-modifiable and modifiable risk factors and resources involved in patients' HF self-care were at the individual and organisational level. Self-efficacy and quality of life are potentially modifiable, so these could be targeted for improvement by enhancing patient motivation, HF education and further supporting a collaborative care approach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
7

Year Published

2012
2012
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(57 citation statements)
references
References 47 publications
5
45
0
7
Order By: Relevance
“…Also, baseline levels of self-care were included as predictors of selfcare at 1-month follow-up in one study (74) and it can be questioned whether self-care is likely to change over such a short period. Self-efficacy was also positively associated with HF self-care behaviors in the remaining studies (16,18,(49)(50)(51)(52)(53)59,(75)(76)(77)(78). One study (52) showed that the relationship between depressive symptoms and treatment adherence was mediated by self-efficacy.…”
Section: Self-efficacy/self-care Confidencementioning
confidence: 85%
“…Also, baseline levels of self-care were included as predictors of selfcare at 1-month follow-up in one study (74) and it can be questioned whether self-care is likely to change over such a short period. Self-efficacy was also positively associated with HF self-care behaviors in the remaining studies (16,18,(49)(50)(51)(52)(53)59,(75)(76)(77)(78). One study (52) showed that the relationship between depressive symptoms and treatment adherence was mediated by self-efficacy.…”
Section: Self-efficacy/self-care Confidencementioning
confidence: 85%
“…Analysis of EHFScBS scores showed that individual resources used in the maintenance of self-care can be targets for constant improvement (12) . Thus, an educational approach to selfcare, coupled with instruments for assessment of this behavior, can be used to identify which determinants are at risk and require intensive or unique management.…”
Section: -Item Version Of the Instrument Developed In Englishmentioning
confidence: 99%
“…Non-experimental studies showed significant correlations between self-efficacy and SM in HF patients(van der Wal. 2010, Bos-Touwen et al 2015a, Peters-Klimm et al 2013, Schnell-Hoehn et al 2009). However, experimental studies failed to demonstrate that increased knowledge and self-efficacy led to increased SM behaviors in HF patients(Riegel.…”
Section: Introductionmentioning
confidence: 99%